Fostering synergy through diversity in multinational project management - Dybchynska, Yana; Volkova, Valeriya (Management and Entrepreneurship: Trends of Development, 2025)
The aim of the study is to analyze the influence of pluralism business context, namely overcoming diversity challenges in international project teams. The specific paper objectives are to review the existing approaches to the concept of diversity; to analyze the concept of diversity management; to outline the possible solutions for achieving the synergetic effect in local operating practices with the purpose of improving business performance of multinational teams. Methodology. The research is an investigation of existing practices aimed at acquiring additional knowledge or idea to raise the level of an existing understanding of the problem of managing cultural diversity in multinational business context. The process for this study has involved a combination of research, synthesis and analysis. Findings. Effectively managing cultural diversity in multinational projects enhances innovation, problem-solving, and decision-making while fostering employee engagement and organizational cohesion. Inclusive organizational cultures that value diverse perspectives support structural and informal integration of minority members, improve talent attraction and retention, and strengthen corporate reputation and financial performance. Applying cultural frameworks such as Hofstede’s, Hall’s, and Trompenaars’ dimensions enables managers to understand team behaviors and tailor strategies to diverse workforces. By addressing challenges such as communication barriers, conflicts, and differing work styles through cross-cultural training, inclusive leadership, and flexible project management, organizations can transform diversity into a strategic advantage, aligning individual and organizational goals and supporting sustainable global operations. JEL Classification: F6, M1, M5